Analisis Tokoh Utama Dalam Novel Konspirasi Alam Semesta Karya Fiersa Besari: Kajian Psikologi Sastra - Putra, Andika Dwi; Arifin, Syaiful; Indrahastuti, Tri (Adjektiva: Educational Languages and Literature Studies, 2020)
This study aims to describe the psychological conflict, psychological aspects, and the factors that influence the psychological aspects of the main character Juang. The results show that the conflict experienced by Juang's character is an external conflict which is divided into conflicts between humans. The conflict is based on the stigma that says that Juang's family is someone traitor to the nation, the internal conflict that Juang experienced was when his friends were busy teasing Nadiya while she was reading a book so she felt disturbed and chose to separate herself from the real world and continue reading her book. The psychological aspect of fighting based on Sigmund Freud's theory works perfectly. The understanding of the id is the most basic personality system, the system that is innate instincts lives with instinctive desires. The fighting ego cannot fulfill the id then the superego works less than perfect and cannot control the id's instinctive desires. Broadly speaking, Juang Juang's psychological turmoil is divided into 2, namely, (1) Factors that influence Juang to be strong in living life as an idealist, including competence motives, love motives, values motives, and attitudes. (2) Factors that influence Juang's feelings include curiosity motives, cultural factors and ecological factors.